Utilization of Health Care Services and Health Seeking Behavior Among Adults of Letang Municipality, Morang, Nepal: An Observational Study - Zobegow, Poba; Adhikari, Shuvechha; Koirala, Asal; Sah, Ranjan Kumar; Yadav, Ranjita (Journal of BP Koirala Institute of Health Sciences, 2024)
Background: Curative services utilization in Nepal was hard hit by Coronavirus disease-19 pandemic in the fiscal year 2077/78. We aimed to compare the state of utilization and health seeking behavior at government and private health care centers post pandemic in a rural area in Eastern Nepal.Methods: A community based cross sectional study included 317 participants who were residing in Letang Municipality of Eastern Nepal  for the past 5 years. Household were selected from three wards out of nine through purposive sampling. Semi structured questionnaire was used to interview the participants.  Binary logistic regression was used to assess independent predictors for health care utilization.Results: Our study revealed half (53.3%) of the households visited the government health care facility. Nine out of ten households were vaccinated against coronavirus disease-19 and about two thirds (63.7%) of them had completed booster dose. Education (p = 0.024), religion (p = 0.001) and preference of health care facility during emergency (p < 0.001)  showed statistically significant association with the type of health facility visited.Conclusion: A significant number of participants had visited the health  care facility several times  during one year with a greater preference towards government health facility during emergency. Good coverage for the Coronavirus disease- 19 vaccination was observed among the study participants.